2021
DOI: 10.3389/fpsyt.2021.684406
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Algorithm to Predict Hazardous Drinkers and the Severity of Alcohol-Related Problems Using K-NHANES

Abstract: Purpose: The number of patients with alcohol-related problems is steadily increasing. A large-scale survey of alcohol-related problems has been conducted. However, studies that predict hazardous drinkers and identify which factors contribute to the prediction are limited. Thus, the purpose of this study was to predict hazardous drinkers and the severity of alcohol-related problems of patients using a deep learning algorithm based on a large-scale survey data.Materials and Methods: Datasets of National Health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The world depression survey conducted in 17 countries found that on average, 1 in 20 people had depression. By 2020, the global disease burden might increase by 5.7%, becoming the second largest disease after ischemic heart disease ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The world depression survey conducted in 17 countries found that on average, 1 in 20 people had depression. By 2020, the global disease burden might increase by 5.7%, becoming the second largest disease after ischemic heart disease ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though R 2 was small, it revealed a significant contribution to the model. Meanwhile, one study that had included 325 variables in 69,187 participants, and implemented deep learning to predict outcome variables (Kim et al, 2021 ). This result suggests that the use of a larger dataset, the inclusion of more predictors, and the implementation of more advanced algorithms will be valuable in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is a type of AI, and it can be altered after exposure to novel data sets and “learn” without new programming (3). In addition, deep learning has been involved in the prediction of certain diseases (5,6).…”
Section: What Is Artificial Intelligence?mentioning
confidence: 99%